Investigation on Solder Joint Strength of Nickel Tin-Plated and CRS Tabs with PCB - B. Hussain, Luay (Malaysian Journal of Science, 2002)
Failure analysis on easily peels off Nickel and CRS steel tabs from PCB was carried out. Nickel Tin plated tabs, CRS steel tabs and tube were joined to the PCB using reflow/ convection soldering in an oven. The solder paste composition is Sn36/Pb35/Ag2. Peel test was conducted and it was found that many tabs could be easily peeled off with low force. Porosities which varies from 0.4 mm to <0.01mm in diameter, developed during soldering process and solidification was noted. It was found, the number, size and position of these porosities inside the solder layer on both parts of the tabs affect the peel strength. Scanning Electron Microscopy study and EDX analysis were carried out. It was found that the low peel strength values were due to the combination of generation and development of porosities during soldering process which act as stress concentrators and the evolution (growth) of eutectic Sn/Pb and SnNi/Cu brittle grainy phase. Large eutectic microstructure with brittle Sn-Ni-Cu grainy phase enhances the failure with low peeling forces. Sample showing no feature of Sn/Ni/Cu grain gave high peeling strength value. Solder reflow, an important process, can result in strength enhancement (if it was controlled for example in a furnace).